Optimization of L-lactic acid production by fermentation of Huaimi dregs. Issue 2 (4th March 2018) - Zhang, Jingsheng; Guo, Zhiyuan; Liu, Bingchen; Wang, Yue; Yu, Na; Huo, Qing
ABSTRACT: Utilization of waste dregs, e.g. Huaimi dregs, is an important issue. Huaimi is a traditional Chinese medicine and 20, 000 tons of dregs are annually produced. This study optimized the production of L-lactic acid through solid-state fermentation of Huaimi dregs using uniform and orthogonal experimental designs. Among three tested parameters, fermentation time and substrate ratio (wheat bran:Huaimi dregs) were found to have a significant effect on the production of lactic acid. Using fermentation time of 41.6 h, substrate ratio of 4.26:1, inoculum size of 6.1% and fermentation temperature of 28 °C, 1 kg Huaimi dregs could produce 286.6 mg lactic acid.